Development of a stroke network in Kinshasa (Democratic Republic of the Congo): a humanitarian project of the Italian Stroke Association—Associazione Italiana Ictus - Benedetti, Lorenzo; Bosenedje, Chadrack; Falcou, Anne; Mabiala, Jonathan; Lumu, René; Ciacciarelli, Antonio; Kashala, Rémy; Toni, Danilo (Frontiers in Stroke, 2024)
In Sub-Saharan Africa (SSA) stroke incidence is of about 316 cases per 100,000 inhabitants(1) and stroke mortality rate is up to 5 times higher compared to High Income Countries (HIC)(2). In 75% of SSA countries, stroke is among the top 3 causes of death. This epidemiological evolution results from the exponential numerical growth of African population associated with the lack of policies for prevention and therapy.The Democratic Republic of Congo (DRC) is one of the countries included in the 2023 OECD (Organization for Economic Cooperation and Development) Development Assistance Committee List under the heading Low Income Country (LIC); its capital is Kinshasa, a megalopolis with more than 18 million of habitants. According to our knowledge, no hospital in Kinshasa is currently capable of admitting and treating patients with stroke in accordance with international guidelines.The Italian Stroke Association (ISA) is the Italian multidisciplinary Scientific Society for the fight against cerebrovascular diseases. Some members of ISA joined to form a working group dedicated to the care of stroke in Africa.In this paper, we will explain the project designed by the ISA Africa Group that, in collaboration with the referral hospital of a district of Kinshasa, has the aim to build-up a network for diagnosis and treatment of stroke, including Ambulance, Stroke Team in Emergency Room, Stroke Unit, Outpatient Clinic and Primary Prevention activities among the population.